Area control error enhancement of two-area power system using hybrid intelligence optimal controller - Muhammad Abdillah; Herlambang Setiadi (Institute of Advanced Engineering and Science, 2023)
Area control error (ACE) is a critical factor in linked power systems. When a disturbance occurs, ACE is utilized to determine how much power should be deployed. As a result, it is critical that the ACE have as little inaccuracy as feasible. This research provided a strategy for improving the dynamic response of ACE in a power system. A hybrid optimal controller is the name given to this technology. Coordination between the proportional-integral (PI) controller and the state feedback controller based on the linear quadratic regulator (LQR) is the concept of a hybrid optimum controller. All controller parameters are created utilizing artificial immune system (AIS) clonal selection to improve coordination. The proposed control mechanism is demonstrated using a two-area power system as a test system. To investigate the efficacy of the suggested strategy, time domain simulation is used. The simulation results show that the suggested method outperforms the previous situations in this work (the overshot of frequency deviation in areas 1 and 2 is 0.00029 and 0.00015, respectively)